Aspectos clínicos e epidemiológicos da Esclerose Lateral Amiotrófica no Estado do Ceará - Fernandes, José Marcelino Aragão (2024)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder that affects motor neurons (upper and lower) causing weakness and progressive muscle atrophy, usually leading to death within 3 to 5 years. In 10 to 15% of cases, the disease is hereditary (familial ALS) and the remaining cases are classified as sporadic ALS. Despite being rare, this disease has major social and economic impacts. The incidence of ALS has been increasing and is estimated to grow more than 60% until 2040. Despite this, there are few population-based studies of ALS in Brazil. We present a descriptive and quantitative study, with a retrospective and prospective design, in patients with ALS followed at the Walter Cantídio University Hospital (HUWC) from January 2013 to December 2023, with the aim of describing the clinical, epidemiological and genetic aspects of ALS in this population, as well as contextualizing it with data from the general population of Ceará. Two hundred forty patients had their medical records analyzed and/or were interviewed from July 2022 to August 2024. Males were the majority with 134 (55.8%) cases, and male to female ratio of 1.3:1. The mean age at the onset of symptoms was 56.39 ± 13.05 years. The sporadic form comprised 92.1% (221) of the cases and the familial form represented 7.9% (19). Limb onset presentation was the most common (72.1%). The genetic diagnosis was conducted in 10 patients, with the mutation in the SOD1 gene (variant: c.358G>C; p.Val120Leu) being the most common (4 patients), leading to a slow clinical course and prolonged survival. Using data from the prescriptions of Riluzole in Ceará, the estimated incidence of ALS was 0.8 and 0.95/100,000/inhabitants in the years 2022 and 2023 respectively. In general, the clinical and epidemiological profile of this study is similar to currents figures in the literature, as well as the estimated incidence is similar to that of other developing countries. The genetic mutations’ profile differs to those described in populations from Europe, the USA, and other national studies, and may reflect the effect of a small sample, restricted to a specific geographic territory and limited genetic testing. However, our findings reinforce that different mutations can be predictors of better or worse prognosis.